Occurrence of paratubal cysts in childhood: An analysis of 26 cases - Bosnalı, Oktav; Moralıoğlu, Serdar; Cerrah-Celayir, Ayşenur (The Turkish Journal of Pediatrics, 2016)
A retrospective analysis was conducted on the case files of patients operated on for adnexal pathology between January 2004 and December 2015 at our institution. The data of the patients with a diagnosis of paratubal cysts (PTCs) was extracted. A total of eighty-seven children were operated on for adnexal pathology. Twenty-six (29.9%) patients had PTCs. The patients were predominantly grouped as adolescents (n=22) and newborns (n=3). One of the patients was a pre-pubertal girl. Of the 26 PTC cases, 18 of them occurred on the contralateral side to ovarian pathology (OP) or physiologic ovarian changes (POC) such as corpus luteum cyst or follicular cyst which their final diagnosis confirmed by histopathology examination; in one case, the PTCs were bilateral; and in three cases, PTCs were ipsilateral with OP or POC. There were only 4 solitary PTC cases identified among the 26 cases. Paratubal cysts can be observed at every age, even in newborns. Their association with OP or POC in childhood cases needs to be clarified to further understand the hormonal mechanisms that are influencing the occurrence of these cysts.
Keywords: adolescent; newborn; ovary; paratubal cyst